Direct seeded rice (DSR) field facilities at IRRI HQ, IRRI South Asia Hub, IRRI ESA (Kenya), AfricaRice (Senegal, Ivory Coast) - CGIAR Research Program on Rice (2021)
The DSR fields have been used at IRRI Headquarters since the wet season of 2021. Field preparation in the Regions are progressing well. Irrigation systems have been ordered and will be installed. All fields are available for use of field experiemnts.